A Remark Related Pseudo-Differential Operators on Multi-Parameter Besov-Lipschitz and Triebel-Lizorkin Spaces. (7th November 2022) - Xu, Chengdan
Abstract : Let a symbol σ x, ξ belongs to the class S 1, 1, δ 1, δ 2 0, 0 with x, ξ ∈ ℝ n 1 × ℝ n 2 and 0 ≤ δ 1, δ 2 < 1 . This paper mainly establish the boundedness of the class of all bi-parameter pseudo-differential operators associated with the symbol σ x, ξ on the multi-parameter non-homogeneous Besov-Lipschitz and Triebel-Lizorkin spaces.